ANALISIS PERRGESERAN STRUKTUR EKONOMI DAN POLA PERTUMBUHAN EKONOMI KOTA PAREPARE - Hatta, Muhammad (Universitas Muhammadiyah Parepare, 2021)
The potential of an area can be identified through the identification of leading sectors. The purpose of this study is to determine the shift in economic structure and patterns of economic growth in Parepare City, using several analytical approaches. This research seeks to analyze and provide information related to shifts in economic structure or solutions to increase economic growth and provide strategic and policy advice. This study is a quantitative descriptive study. The data used is secondary data. Data analysis techniques were carried out through literature studies and publications published by BPS. Then the data were analyzed using Location Quotient (LQ) analysis tools, Shift Share analysis, and Klassen Typology analysis. The results of the study indicate that there has been a shift in the economic structure from agriculture (primary sector) and industry (secondary sector) to the service sector (tertiary sector) while the economic sectors that are included in the developed sector and grow rapidly in the first quadrant are Electricity Procurement and Gas, Water Supply, Waste Treatment, Waste and Recycling, Transportation and Warehousing, Provision of Accommodation and Food and Drink, Financial and Insurance Services, Real Estate, Health Services, and Social Activities., Corporate Services. The results of the Shift Share analysis show that there has been a shift in the economic structure. from industry (secondary) to services (tertiary). Location quotient (LQ) analysis results show that the base sector includes fourteen sectors including four industrial sectors and nine service sectors, while the non-base sector has four sectors.